2015
DOI: 10.1017/s136898001500083x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in pre-school children in rural Nepal

Abstract: Objective: Vitamin D plays a major role in Ca and bone metabolism, and its extraskeletal functions are being appraised. Although inadequate vitamin D concentrations have been reported in populations worldwide, too little is known about vitamin D status and its determinants among children in developing countries. We aimed to determine vitamin D status and its determinants in Nepalese children of pre-school age. Design: A community-based, cross-sectional study. Setting: Rural Nepal at latitude 27·39°N. Subjects:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
2
28
3
Order By: Relevance
“…The prevalence of insufficiency and deficiency was 2.5-fold higher in studies that included children with pneumonia compared with that in the population of healthy infants. The prevalence of poor vitamin D status was lower in the present study compared with that in other studies of healthy children in Nepal (12,32). There are currently no government programs or recommendations of vitamin D supplementation or food fortification for infants in Nepal (17,33).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The prevalence of insufficiency and deficiency was 2.5-fold higher in studies that included children with pneumonia compared with that in the population of healthy infants. The prevalence of poor vitamin D status was lower in the present study compared with that in other studies of healthy children in Nepal (12,32). There are currently no government programs or recommendations of vitamin D supplementation or food fortification for infants in Nepal (17,33).…”
Section: Discussioncontrasting
confidence: 74%
“…Exclusive breast-feeding has been considered inadequate to prevent vitamin D deficiency (13,34), but recent reports show that vitamin D content in human milk is highly dependent on the mother's vitamin D status (35,36). Local sun-exposure habits associated with breast-feeding in Nepal, such as outdoor breast-feeding (12) and the tradition of sunbathing infants younger than 3 months (37), may therefore be plausible explanations for the relatively high plasma 25(OH)D concentration found in this study. We also found a stable plasma 25(OH)D concentration throughout the year, which may reflect adequate skin-synthesis of vitamin D across the seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural practices may impact vitamin D status in otherwise healthy populations, best illustrated in cultures where women cover their bodies and heads and/or spend a lot of time indoors [1,2,3,4,5]. There are also reports of poor vitamin D status among otherwise healthy populations in Nepal [6,7,8], despite over 300 sunny days a year [9], and no cultural avoidance of the sun. The increasing awareness of possible “extra-skeletal effects” of vitamin D on outcomes such as development of malignant, cardiovascular, autoimmune, metabolic and infectious diseases [10], and pregnancy outcomes and child growth [11], has resulted in an ongoing debate about optimal levels of vitamin D and an increased effort to identify predictors and implications of poor vitamin D status.…”
Section: Introductionmentioning
confidence: 99%
“…5 Similarly an overall prevalence of 40%, with a higher (64.8% ) deficiency status among the adolescent girls, was reported in a study with 110 children in Ankara, Turkey 2 Prevalence is almost similar to a study by S Shrestha et al in Lalitpur Nepal, and they have reported prevalence of 78.2% among the young adults. 12 McGillivray et al reported 87% prevalence in East African immigrants living in Melbourne 21 and 90.8% prevalence reported by an Indian study among school aged girls is higher than the Shrestha's series 5,20 In our study, the comparisons between age groups in terms of Vitamin D levels revealed a very high 95.2% prevalence of vitamin deficiency/insufficiency among school aged children (6-10 yr) followed by 79.2% in adolescents (11-19yr). The cause behind such a high rate may be due to enrollment of entire symptomatic children, more indoor engagement, less sun exposure, air pollution and lack of vitamin supplementation.…”
Section: Resultsmentioning
confidence: 94%